Facial harmony after orthognatic surgery in patients with laterognati (case series) - BAYRAM, FERİT; ÖZKAN, YAŞAR (My University, 2023)
Objective: Providing ideal aesthetics and function in cases with dentofacial deformity and laterognathism is quite complex. Mostly in Class III patients, lower incisors tend to tip lingually and maxillary incisors labially to compansate the occlusion. With addition of laterognathism, improving the occlusal relation, chewing function and profile aesthetics gets even more challenging. For such adult patient cases, orthognathic bilateral sagittal split osteotomy can be used to reposition the jaws to their ideal locations, but it is crucial to take into consideration the patient’s post op occlusal functions and stability, profile and facial appearance preferences during the treatment planning. To achieve the ideal results, you need to plan in a multidiciplinary aspect, patients need to go under orthodontic decompansation treatment to have their ideal dental positions in the alveolar bone. In this case series, we aim to emphasize the importance of the collaboration between orthodontics and surgery in patients with laterognathism and facial disharmony. Materials-Method: In this study three high angle Class III patients with 1-4 mm of mandibular deviation were selected. To correct the angulation and alignment of the teeth first; before the surgery they had an orthodontic treatment; so, after the surgery, it would be easier to have stable occlusion. The patients underwent bilateral sagital split osteotomy. The orthognathic surgery performed by the Department of Oral and Maxillofacial Surgery at Marmara University Faculty of Dentistry between 2019 and 2022. Digital planning was initially conducted for our patients, and the expected outcomes and facial changes were communicated to them. Subsequently, the surgeries were performed according to the planned adjustments and the splints created for each patient, and aesthetic changes after surgery were evaluated. Conclusion: The results showed that good occlusal relation, and sufficient alveolar bone support was present around the teeth, dental inclinations, soft tissue profile and overall an aesthetic improvement was achieved as planned. This study shows with a multidisiplinary approach and a up to date technological planning, we can predict more precisley our treatment results to increase the aesthetic and functional quality for our patients. To further validate our results, it is necessary to increase the number of patients and conduct clinical trials with longer follow-up periods.
Keywords: Diş Hekimliği; Klinik Bilimler; Ağız, Diş-Çene Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Dentistry; Clinical Sciences; Oral, Maxillofacial and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry